2017
DOI: 10.1002/glia.23212
|View full text |Cite
|
Sign up to set email alerts
|

Reactive astrocyte COX2‐PGE2 production inhibits oligodendrocyte maturation in neonatal white matter injury

Abstract: Inflammation is a major risk factor for neonatal white matter injury (NWMI), which is associated with later development of cerebral palsy. Although recent studies have demonstrated maturation arrest of oligodendrocyte progenitor cells (OPCs) in NWMI, the identity of inflammatory mediators with direct effects on OPCs has been unclear. Here, we investigated downstream effects of pro-inflammatory IL-1β to induce cyclooxygenase-2 (COX2) and prostaglandin E2 (PGE2) production in white matter. First, we assessed COX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 73 publications
(108 reference statements)
3
100
0
Order By: Relevance
“…Overall the data in this study on neuropathological findings and neuroinflammatory events associated with neuroinflammation alone was similar to what we have published previously (Favrais et al, 2011;Krishnan et al, 2017;Schang et al, 2014;Shiow et al, 2017;Van Steenwinckel et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall the data in this study on neuropathological findings and neuroinflammatory events associated with neuroinflammation alone was similar to what we have published previously (Favrais et al, 2011;Krishnan et al, 2017;Schang et al, 2014;Shiow et al, 2017;Van Steenwinckel et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Use of P1-P5 mice to model the preterm infant brain is supported by comparative studies of brain growth and oligodendrocyte maturation (Back et al, 2001;Dean et al, 2011;Dobbing and Sands, 1979) and reviewed in (Semple et al, 2013). Full descriptions of the model including systemic and central inflammatory response and neuropathology are available within these references (Favrais et al, 2011;Krishnan et al, 2017;Schang et al, 2014;Shiow et al, 2017;Van Steenwinckel et al, 2018).…”
Section: Potential Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…At P3, brains were collected for cell dissociation and CD11B+ cell separation using a magnetic coupled antibody anti-CD11B (Miltenyi, MACS Technology) as previously described in detail (Krishnan et al, 2017;Schang et al, 2014;Shiow et al, 2017). Microglia are the predominant CD11B cell in this model of injury by more than 100-fold compared with populations of either macrophage or neurtrophil (Krishnan et al, 2017).…”
Section: Isolation and Ex Vivo Microglia And Gene Expression Analysismentioning
confidence: 99%
“…We further studied MG/Mφ activation using expression analysis of sixteen genes and six protein markers previously associated with polarized expression states (Chhor et al 2013, Miron et al 2013 at 5 time points. Gene expression analysis was performed in CD11B+ cells isolated by magnetically activated cell sorting (MACS, Miltenyi Biotec) from PBS-or IL-1β-exposed mice as per our previous studies (Chhor et al 2017, Krishnan et al 2017, Shiow et al 2017. Prior FACS analysis has demonstrated that the ratio of MG to other CD11B+ cells in this isolate is greater than 50 to 1 (Krishnan et al 2017).…”
Section: Mg Activation Is Persistent With Specific Temporal Patterns mentioning
confidence: 99%